Statistical mechanics study of the thermodynamics of binary alloys with long-rang interaction - Danilova, L.P.; Virchenko, Yu.P. (Functional Materials, 2018)
In frameworks of statistical mechanics of lattice gas model, it is calculated the free energy and the specific heat of binary alloys in the case when their atoms have a long-rang interaction. The calculation method is based on the use of connection between the statistical system of alloy atoms and the so-called lattice gas model. For the analysis of temperature dependence of each term in lattice gas virial expansion it is applied its decomposition on Ursell's function degree. Such an approximation method represents a modification of high temperature expansions of various model thermodynamic characteristics.